2019
DOI: 10.24198/pjd.vol31no3.19328
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ant-plant (Hydnophytum formicarum) ethanol extract on collagen fibers for wound healing after tooth extraction in the guinea pig (Cavia cobaya)

Abstract: Introduction: Tooth extraction causes tissue damage around the socket. Wound healing is essential for repairing damaged tissues. One of the medicinal plants often used is ant-plant (Hydnophytum formicarum), which contains flavonoids, triterpenoids, saponins and tannins. This research was aimed to determine the effect of ant-plant ethanol extract on the density of collagen fibers for wound healing after tooth extraction in the guinea pig (Cavia cobaya). Methods: The type of research was true experimental with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
1
1
Order By: Relevance
“…9,10 A study conducted by Velanita et al found that the ad ministration of the Hydnophytum formicarum plant ex tract orally at a dose of 4.65 mg was able to significantly increase the production of collagen fibers in wound heal ing in the oral cavity after tooth extraction. 11 This is in contrast to the results of the present study, which indi cated that collagen density in the control and treatment groups did not present significantly different values, although there was a statistically significant interaction between the use of the extract and the necropsy day, af fecting collagen density. This interaction indicates that the Hydnophytum formicarum plant extract may change the value of collagen density when used for 14 days.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…9,10 A study conducted by Velanita et al found that the ad ministration of the Hydnophytum formicarum plant ex tract orally at a dose of 4.65 mg was able to significantly increase the production of collagen fibers in wound heal ing in the oral cavity after tooth extraction. 11 This is in contrast to the results of the present study, which indi cated that collagen density in the control and treatment groups did not present significantly different values, although there was a statistically significant interaction between the use of the extract and the necropsy day, af fecting collagen density. This interaction indicates that the Hydnophytum formicarum plant extract may change the value of collagen density when used for 14 days.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the extract was applied topically, whereas in previous studies, it was administered orally. 9,11 With regard to angiogenesis, this study indicates that the topically applied Hydnophytum formicarum plant extract can significantly reduce angiogenesis that occurs during the early, middle and late prolifera tion phases. This result is consistent with research by Ismardianita et al, who concluded that the oral adminis tration of the Hydnophytum formicarum plant extract at a dose of 6.2 mg was able to significantly reduce angio genesis in the proliferation phase.…”
Section: Discussionmentioning
confidence: 78%